2018
DOI: 10.5430/jnep.v8n8p12
|View full text |Cite
|
Sign up to set email alerts
|

Saudi female university employee self-determination in their own health-related issues

Abstract: Introduction: To date, there have been no studies located investigating Saudi women's self-determination in their own healthrelated issues. This study aims to investigate how women in Saudi Arabia see their ability and willingness to decision making in this matter. Methodology: The study design is ethnonursing and Leininger's Sunrise model was utilized as background theory; qualitative data analysis method was used. 12 Saudi women worked at a large University in Saudi Arabia were interviewed in-depth. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Regarding to nursing student's knowledge about woman right to health the present study shows that majority of studied sample had incorrect knowledge during preintervention and had improvement of knowledge in immediate post intervention and 8 weeks post intervention. This finding was agreed with Hallila, & Al-Halabi [25], they studied Saudi female university employee self-determination in their own healthrelated issues and revealed that most of the participants did not fully understand the health rights of women in Saudi Arabia.…”
Section: Regarding To Sociodemographic Characteristics Of Adolescentsupporting
confidence: 89%
“…Regarding to nursing student's knowledge about woman right to health the present study shows that majority of studied sample had incorrect knowledge during preintervention and had improvement of knowledge in immediate post intervention and 8 weeks post intervention. This finding was agreed with Hallila, & Al-Halabi [25], they studied Saudi female university employee self-determination in their own healthrelated issues and revealed that most of the participants did not fully understand the health rights of women in Saudi Arabia.…”
Section: Regarding To Sociodemographic Characteristics Of Adolescentsupporting
confidence: 89%